Phosphate glass fibre reinforced composite for bone repair applications: investigation of interfacial integrity improvements via chemical treatments - Hasan, Muhammad Sami (2012)
Bone repair devices made from degradable polymers, such as poly lactic acid (PLA) have limitation in terms of matching the mechanical property requirements for bone repair, both initially and for the duration of repair. For this reason the use of totally degradable phosphate glass fibre (PGF) reinforced PLA composite has proved attractive. A crucial part of the success of such implants is maintenance of interfacial integrity between the polymer matrix and reinforcement phases of the composite. It is well known that most fibre reinforced composites loose 50% or more of their strength due to interfacial integrity loss. In this study candidate chemical treatments for PGF reinforced PLA composite are being investigated in terms of their reactability, biocompatibility, effect on interfacial mechanical properties and degradation behaviour of these composites.